The Influence of Road Geometry on the Number of Accidents at Curves: A Study on the Variability of Hilliness and Bendiness - Putri, Atissa Dwi; Siregar, Martha Leni; Soehodho, Sutanto (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2025)
This study examined the influence of roadway geometry on traffic safety, focusing on the effects of hilliness and bendiness along a 9.28 km road segment in West Sumatra, Indonesia. Geometric data, including elevation and curvature, were collected using the GeoTracker application and processed with a Python-based sliding window segmentation of 1 km length and 50% overlap, resulting in 19 analysis segments. Traffic accident data were obtained from official police reports and included the number of crashes, minor injuries, serious injuries, and fatalities for each segment. Multivariate Analysis of Variance (MANOVA) was performed to evaluate the simultaneous effects of hilliness and bendiness on the crash variables. The results showed that hilliness significantly influenced the total number of accidents, while bendiness significantly affected the occurrence of serious injuries. Hilliness explained approximately 80% of the variance in accident frequency, and bendiness contributed substantially to variations in serious injuries. Although neither hilliness nor bendiness showed significant effects on minor injuries and fatalities, both factors exhibited positive trends in relation to increasing crash severity. The findings demonstrated that vertical elevation changes and horizontal curvature contributed significantly to traffic accident risks. The study suggested that incorporating these geometric parameters into road design, safety assessments, and targeted interventions could help reduce accident occurrences, particularly in mountainous and curvilinear roadway segments.